Cardiovascular risk factors and comorbidities in people living with HIV: A cross-sectional multicenter study from Colombia comorbidities in a Colombian PLWHIV population. (June 2022) - Valderrama-Beltrán, Sandra; Martínez-Vernaza, Samuel; Figueredo, María; Martínez, Ernesto; Blair, Kevin J; Cuervo-Rojas, Juliana; Arévalo, Leonardo; De La Hoz, Alejandro; Quiroga, Camilo; Mueses, Héctor; Sussmann, Otto; Mantilla, Mónica; et al.
Introduction: HIV is an independent risk factor for cardiovascular diseases (CVD). There is insufficient information regarding comorbidities and cardiovascular risk factors in the Colombian HIV population. The aim of this study is to describe the prevalence of cardiovascular risk factors and comorbidities in patients from the HIV Colombian Group VIHCOL. Methods: This is a multicenter, cross-sectional study conducted in the VIHCOL network in Colombia. Patients 18 years or older who had at least 6 months of follow-up were included. A stratified random sampling was performed to estimate the adjusted prevalence of cardiovascular risk factors and comorbidities. Results: A total of 1616 patients were included. 83.2% were men, and the median age was 34 years. The adjusted prevalence for dyslipidemia, active tobacco use, hypothyroidism, and arterial hypertension was 51.2% (99% CI: 48.0%–54.4%), 7.6% (99% CI: 5.9%–9.3%), 7.4% (99% CI: 5.7%–9.1%), and 6.3% (99% CI: 4.8%–7.9%), respectively. Conclusions: In this Colombian HIV cohort, there is a high prevalence of modifiable CVD risk factors such as dyslipidemia and active smoking. Non-pharmacological and pharmacological measures for the prevention and management of these risk factors should be reinforced.